Computed Tomography Advanced Applications - Mesrur Halefoglu, Ahmet (IntechOpen, 2017)
The advent and rapid diffusion of advanced multidetector-row scanner technology offers comprehensive evaluation of different anatomic structures in daily practice. The aim of this book is to introduce the applications of CT imaging in not only general medicine but also in different fields especially in veterinary medicine, dentistry, and engineering. Recent developments in CT technology have led to a widening of its applications on many areas like material testing in engineering, 3D evaluation of teeth, and the vascular and cardiac evaluations of small animals.